Changing global policy to deliver safe, equitable, and affordable care for women's cancers. Issue 10071 (25th February 2017) - Ginsburg, Ophira; Badwe, Rajan; Boyle, Peter; Derricks, Gemma; Dare, Anna; Evans, Tim; Eniu, Alexandru; Jimenez, Jorge; Kutluk, Tezer; Lopes, Gilberto; Mohammed, Sulma I; Qiao, You-Lin; et al.
Summary: Breast and cervical cancer are major threats to the health of women globally, particularly in low-income and middle-income countries. Radical progress to close the global cancer divide for women requires not only evidence-based policy making, but also broad multisectoral collaboration that capitalises on recent progress in the associated domains of women's health and innovative public health approaches to cancer care and control. Such multisectoral collaboration can serve to build health systems for cancer, and more broadly for primary care, surgery, and pathology. This Series paper explores the global health and public policy landscapes that intersect with women's health and global cancer control, with new approaches to bringing policy to action. Cancer is a major global social and political priority, and women's cancers are not only a tractable socioeconomic policy target in themselves, but also an important Trojan horse to drive improved cancer control and care.